Las vicisitudes de la ecobiopolítica. Capitaloceno, dispositivo extractivo y crisis del habitar - Rodríguez Rojas, Juan Manuel (2025)
In the current panorama of social, subjective, political, and inhabitation crises, this article seeks to reflect on the current state of power and the mechanisms through which life is produced and organized. First, it proposes the concept of ecobiopolitics as a concept that would allow us to understand how power serves the production of space and human and extrahuman inhabitation. Itthen demonstrates how extractivism, as the central organizing mechanism of this power, has ultimately put the habitability of the Earth in crisis for both human beings and extrahuman life.